Atomic Layer Deposition of Textured Li4Ti5O12: A High‐Power and Long‐Cycle Life Anode for Lithium‐Ion Thin‐Film Batteries. Issue 34 (17th July 2021) - Speulmanns, Jan; Kia, Alireza M.; Bönhardt, Sascha; Weinreich, Wenke; Adelhelm, Philipp
Abstract: The "zero‐strain" Li4 Ti5 O12 is an attractive anode material for 3D solid‐state thin‐film batteries (TFB) to power upcoming autonomous sensor systems. Herein, Li4 Ti5 O12 thin films fabricated by atomic layer deposition (ALD) are electrochemically evaluated for the first time. The developed ALD process with a growth per cycle of 0.6 Å cycle −1 at 300 °C enables high‐quality and dense spinel films with superior adhesion after annealing. The short lithium‐ion diffusion pathways of the nanostructured 30 nm films result in excellent electrochemical properties. Planar films reveal 98% of the theoretical capacity with 588 mAh cm −3 at 1 C. Substrate‐dependent film texture is identified as a key tuning parameter for exceptional C‐rate performance. The highly parallel grains of a strong out‐of‐plane (111)‐texture allow capacities of 278 mAh cm −3 at extreme rates of 200 C. Outstanding cycle performance is demonstrated, resulting in 97.9% capacity retention of the initial 366 mAh cm −3 after 1000 cycles at 100 C. Compared to other deposition techniques, the superior performance of ALD Li4 Ti5 O12 is a breakthrough towards scalable high‐power 3D TFBs. Abstract : Li4 Ti5 O12 is an attractive anode for lithium‐ion thin‐film batteries. Nanostructured 30 nm films fabricated by atomic layer deposition enable excellent electrochemical properties. Film texture is an important tuning parameter for the high‐power performance, reaching exceptional 278 mAh cm −3 at extreme rates of 200 C. Only 2.1% capacity loss after 1000 cycles at 100 C demonstrates outstanding cycle performance.